2020
DOI: 10.1159/000511003
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphologic Features of Gastric-Type Endocervical Adenocarcinoma in Liquid-Based Preparations

Abstract: <b><i>Objective:</i></b> Gastric-type endocervical adenocarcinoma (GAS) is a recently described, uncommon, and aggressive tumor with distinct morphologic features and HPV-independent etiology. Data on GAS in liquid-based cytology (LBC) Papanicolaou (Pap) test preparations from a North American patient population are scant. We systematically assessed the cytomorphologic characteristics of GAS in LBC from patients in Ontario and examined if glandular cell nuclear area could represent a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…In the present study, preoperative cytologic diagnoses included AGCs, favor neoplastic in three cases, AIS in one case, and adenocarcinoma in four cases. Preoperative cytologic diagnoses of the previously reported GEA cases were reviewed [11][12][13]15] including the eight cases used in this study (Table 4). Among a total of 56 cases, the original cytologic interpretations were the following: negative for intraepi- thelial lesion or malignancy (n = 10, 17.9%); AGC, not otherwise specified/favor neoplastic (n = 16, 28.6%); AIS (n = 3, 5.4%); high-grade squamous intraepithelial lesion (n = 1, 1.8%); adenocarcinoma (n = 25, 44.6%); unsatisfactory for evaluation (n = 1, 1.8%) (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, preoperative cytologic diagnoses included AGCs, favor neoplastic in three cases, AIS in one case, and adenocarcinoma in four cases. Preoperative cytologic diagnoses of the previously reported GEA cases were reviewed [11][12][13]15] including the eight cases used in this study (Table 4). Among a total of 56 cases, the original cytologic interpretations were the following: negative for intraepi- thelial lesion or malignancy (n = 10, 17.9%); AGC, not otherwise specified/favor neoplastic (n = 16, 28.6%); AIS (n = 3, 5.4%); high-grade squamous intraepithelial lesion (n = 1, 1.8%); adenocarcinoma (n = 25, 44.6%); unsatisfactory for evaluation (n = 1, 1.8%) (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Using LBP, tall columnar epithelial cells with pale, foamy or vacuolated cytoplasm were the most common cytologic findings of GEA, followed by well-defined cytoplasmic borders [ 11 ]. Recently, Schwock et al [ 13 ] reported cytomorphologic features of GEA based on LBP. The most discriminatory findings for GEA versus UEA were microvesicular cytoplasm (100% vs. 17%), honeycomb-like sheets (87% vs. 8%), prominent nucleoli (93% vs. 25%), and anisonucleosis (93% vs. 50%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…В мировой практике цитологический метод диагностики эндоцервикальных аденокарцином используется достаточно широко. Об этом свидетельствуют появившиеся работы, касающиеся не только диагностики, но и возможностей дифференцирования типов эндоцервикальных аденокарцином по цитологическим препаратам, о чем свидетельствуют научные статьи [26][27][28][29][30].…”
Section: опухоли женской репродуктивной системы Tumors Of Female Repr...unclassified